1997
DOI: 10.1161/01.cir.95.5.1278
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tolerance of the Chronically Hypoxic Immature Heart to Ischemia

Abstract: Increased tolerance to ischemia exhibited by chronically hypoxic rabbit hearts is associated with increased activation of the KATP channel. This increased KATP activity may be the result of increased intracellular concentrations of lactate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 19 publications
4
68
1
Order By: Relevance
“…Cardiac output was similar in all groups, except for group 9, where cardiac output was lower than that of group 8. The heart rate in group 1 was lower than in groups 3,7,8,10, and 11. LV external heart work in groups 1, 2, 5, and 6 and RV external heart work in the other groups were not different from each other ( Table 4).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Cardiac output was similar in all groups, except for group 9, where cardiac output was lower than that of group 8. The heart rate in group 1 was lower than in groups 3,7,8,10, and 11. LV external heart work in groups 1, 2, 5, and 6 and RV external heart work in the other groups were not different from each other ( Table 4).…”
Section: Resultsmentioning
confidence: 69%
“…A prior study (3) in immature rabbit hearts demonstrated postischemic recoveries of hypoxic RVs and LVs that were similarly improved over those of the respective normoxic controls. In contrast, in the present study using adult rat hearts, chronic hypoxia improved postischemic RV but not LV func- Values are means Ϯ SE; n, no.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Experimental studies in the newborn heart suggest a lower tolerance of the LV to ischemia, as LV recovery of function following ischemia is far worse than that seen in the RV (3). Whether these findings are a result of ventricle-specific differences in postnatal myocardial metabolic maturation is currently unknown.…”
mentioning
confidence: 99%